Spectral analysis of the emission current noise exhibited by few layer WS2 nanosheets emitter - Suryawanshi, Sachin R.; Kolhe, Pankaj S.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Ultramicroscopy, 2015)
Spectral analysis of the field emission (FE) current fluctuations has been carried out at the base pressure similar to 1 x 10(-8) mbar. The emission current stability investigated at preset value of 2 mu A is characterized by `step like fluctuation. The spectral analysis performed on a FFT (Fast Fourier Transform) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha as similar to 1.05. The estimated value of alpha implies that the current fluctuations are mainly due the various processes occurring on atomic scale like adsorption, migration, and/or desorption of the residual gas species on the emitter surface. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Current fluctuations; field emission; Noise; WS2 nanosheets

Stable field emission from layered MoS2 nanosheets in high vacuum and observation of 1/f noise - Kashid, Ranjit V.; Joag, Pracheetee D.; Thripuranthaka, M.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Nanomaterials and Nanotechnology, 2015)
Field emission and current noise of hydrothermally synthesized MoS2 nanosheets are investigated in ultra-high-vacuum and industrially suited high-vacuum conditions. The study reveals that the emission turn-on field is pressure dependent. Moreover, the MoS2 nanosheets exhibit more stable field-electron emission in high-vacuum than in ultra-high-vacuum conditions. The investigations on field-emission current fluctuations show features of 1/f-type noise in ultra-high-vacuum and high-vacuum conditions, attributed to adsorption and desorption processes. The post-field-emission results indicate the MoS2 nanosheets are a robust field emitter in high-vacuum conditions.
Keywords: Electron emission; layered materials; MoS2; Noise measurement; Raman spectroscopy

Future prospects of 2D materials for sensing applications - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
Two-dimensional (2D) material attracted significant research interest from the discovery of graphene in 2004. These 2D materials allow a platform for artificial integration of heterostructures with unique platforms that show exotic physical attributes and phenomenon as well as properties and applications. Each layer in 2D materials consist of a covalent bond, a dangling bond-free lattice, and weak van der Waals (vdWs) interaction. This makes it feasible to fabricate lateral and vertical vdWs heterostructures without the constraints of lattice matching and processing compatibility. These vdWs heterostructures open a door for a broad range of applications in electronics, optoelectronics, flexible devices, sensors, and photovoltaics. In this chapter, we have critically assessed the recent developments in 2D materials, the fabrication of heterostructures, and their application for sensing purposes. We conclude with current challenges and ideas concerning future developments in this merging field.

Introduction - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
The book provides comprehensive and updated research contribution about advances in synthesis/growth of 2D materials for various sensor applications, their working principles, and mechanism behind the sensor as well physics and chemistry of materials.